Competence-based performance evaluation in a hospital institution: nurses’ experience (Research, Society and Development, 2020)
Objective: to know the nurses’ experience in the implementation of the competence-based performance evaluation system in a hospital institution. Method: descriptive, qualitative study, developed with 20 nurses from a hospital. The data was collected between November and December 2018, through semi-structured interviews, and were subjected to thematic content analysis. Results: Three categories emerged: management by competencies, considerations about implantation in the institution; the evaluation process from the perspective of nurses, inherent understandings; and, competency-based performance evaluation, impacts perceived by nurses on nursing technicians. Conclusion: Competency-based performance evaluation applied in the context of the nursing service in a hospital, favors the development of nurses as team managers and contributes to the planning and proposition of plans for the development of skills in nursing technicians, reflecting on quality and safety of patient care.